2022
DOI: 10.1080/23248378.2022.2029723
|View full text |Cite
|
Sign up to set email alerts
|

On the modelling of the friction characteristics of railway vehicle brakes

Abstract: The rules and standards that define the requirements and methods for the layout of friction brake systems for railway vehicles still demand extensive experimental surveys since the general confidence in the theoretical predictability of the brake pad friction behaviour is limited. In fact, a review of numerous measurements from dynamometer test rigs exposes a large variation of the friction characteristics. Nevertheless, these measurements could be exploited to develop an elaborate friction modelling approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Meanwhile, by using a known vehicle velocity and a known brake force, the brake temperature model developed in Section 3 can be used to calculate the temperature at the wheel-shoe interface. Various publications 914 have indicated that temperature has influences on brake CoF. An example format of the CoF variation formula can be expressed as 9 :where μb0 is the kinetic CoF (lowest value); nv and mv are two parameters to describe the CoF variation with vehicle velocity v; nt and mt are two parameters to describe the CoF variation with temperature.…”
Section: Combining Brake Shoe Temperature and Ltd Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, by using a known vehicle velocity and a known brake force, the brake temperature model developed in Section 3 can be used to calculate the temperature at the wheel-shoe interface. Various publications 914 have indicated that temperature has influences on brake CoF. An example format of the CoF variation formula can be expressed as 9 :where μb0 is the kinetic CoF (lowest value); nv and mv are two parameters to describe the CoF variation with vehicle velocity v; nt and mt are two parameters to describe the CoF variation with temperature.…”
Section: Combining Brake Shoe Temperature and Ltd Modelsmentioning
confidence: 99%
“…Meanwhile, by using a known vehicle velocity and a known brake force, the brake temperature model developed in Section 3 can be used to calculate the temperature at the wheel-shoe interface. Various publications [9][10][11][12][13][14] have indicated that temperature has influences on brake CoF. An example format of the CoF variation formula can be expressed as 9 :…”
Section: Combining Brake Shoe Temperature and Ltd Modelsmentioning
confidence: 99%
See 1 more Smart Citation